Responsiveness of the child perceptions questionnaire (11-14) for Cambodian children undergoing basic dental care - Turton, B.J.; Thomson, W.M.; Page, L.A.F.; Saub, R.; Ishak, A.R. (Blackwell Publishing, 2014)
BackgroundOral-Health-Related Quality of Life (OHRQoL) instruments are useful outcome measures in dental health services research; however, there are no reports of the use OHRQoL measures in evaluating the outcome of basic dental care in children anywhere. AimThe aims of this study are to evaluate the responsiveness of the Khmer version of the Child Perceptions Questionnaire(11-14) (CPQ(11-14)) and to describe changes in OHRQoL associated with the provision of basic dental care. DesignA pre-test/post-test design, with a clinical convenience sample of children aged from 8 to 14 years of age who received basic dental care from a local nongovernmental organisation (NGO). ResultsOf the 140 children in the baseline sample, 116 (82.9%) were followed up. The mean change in CPQ(11-14) overall score for those with caries was 1.7, representing a small improvement in OHRQoL. There was a moderate (one in three) statistically significant reduction in the prevalence of impacts across the whole sample (P<0.001; McNemar test), and one in five improved by the minimally important difference (MID) of five-scale points. ConclusionsThe Khmer version of the CPQ(11-14) appears to be a valid and responsive measure for assessing treatment-associated changes in OHRQoL in children with dental caries in Cambodia.